Android for Work Productivity for Professionals - Karch, Marziah; Anglin, Steve; Pundick, Douglas; Andres, Clay.; Beckner, Mark.; Buckingham, Ewan.; Cornell, Gary.; Gennick, Jonathan; Hassell, Jonathan; Lowman, Michelle; Moodie, Matthew; Parkes, Duncan; et al. (Berkeley, CA : Apress, 2010)
Android is new, Android is open, and Android is fun. It$1 (Bs also serious about business. Android for Work shows you how to harness the power of Android to stay productive and take your office on the road. This book also sheds light on the often daunting task of finding the right Android phone for the business user. Whether this is your first smartphone, your first Android smartphone, or your first attempt to make your phone into a productivity tool, Android for Work gets you started. You$1 (Bll learn how to manage email and tasks, but you$1 (Bll also learn how to weed through the sea of games to find specialized productivity tools for a variety of professions. For those that are more interested in an enterprise wide deployment, the book includes an appendix of information on administering Android phones, creating custom interfaces, and creating specialized apps for your enterprise. You$1 (Bll also learn more about integrating Android with other Google Apps for enterprise.s
Buying and Activating an Android Phone -- Using Your Phone for the First Time -- Going Online with Android -- Android Calling -- Managing Texting -- Wrangling Your E-mail -- The Calendar -- Android in a Microsoft World -- Photos and Video -- Web Browsing -- Social Media and Work -- Maps and Mobile -- The Remaining Android Apps -- The Android Market -- General Business Applications -- Specialized Apps for Professionals -- Advanced Customization and Troubleshooting.
Keywords: Computer science; Computer Science; Computer Science, general